Maintenance management at water treatment plant / Nurul Ashikin Baharum - Baharum, Nurul Ashikin (Faculty of Architecture, Planning and Surveying, 2010)
The maintenance management is very important for company especially and to get the proper maintenance the organization should be have the best of software maintenance management to control all matter such as maintenance. The objective of the study is to identify the maintenance management water treatment plant by Puncak Niaga and to compare water treatment system in term of quality. The data was collected by literature review, observation, and interview with plant manager and the person who involve in maintenance work. In identify the maintenance management water treatment plant and comparison of water treatment system in term quality, the research was done at water treatment plant Bukit Nanas Kuala Lumpur, Sg Selangor Phase 2 Batang Beijuntai Selangor, Wangsa Maju Kuala Lumpur and Sg Rumput Gombak Selangor. The findings were that each water treatment has different maintenance management even all of water treatment plants are under by Puncak Niaga. However, all the water treatment plant are stay following the standard and guidelines from Puncak Niaga.